Biocontrol Traits Correlate With Resistance to Predation by Protists in Soil Pseudomonads - Amacker, Nathalie; Gao, Zhilei; Agaras, Betina C.; Latz, Ellen; Kowalchuk, George A.; Valverde, Claudio F.; Jousset, Alexandre; Weidner, Simone (Frontiers in Microbiology, 2020)
Root-colonizing bacteria can support plant growth and help fend off pathogens. While it is clear that such bacteria benefit from plant-derived carbon, it remains ambiguous why they invest in plant-beneficial traits. We suggest that selection via protist predation contributes to recruitment of plant-beneficial traits in rhizosphere bacteria. To this end, we examined the extent to which bacterial traits associated with pathogen inhibition coincide with resistance to protist predation. We investigated the resistance to predation of a collection of Pseudomonas spp. against a range of representative soil protists covering three eukaryotic supergroups. We then examined whether patterns of resistance to predation could be explained by functional traits related to plant growth promotion, disease suppression and root colonization success. We observed a strong correlation between resistance to predation and phytopathogen inhibition. In addition, our analysis highlighted an important contribution of lytic enzymes and motility traits to resist predation by protists. We conclude that the widespread occurrence of plant-protective traits in the rhizosphere microbiome may be driven by the evolutionary pressure for resistance against predation by protists. Protists may therefore act as microbiome regulators promoting native bacteria involved in plant protection against diseases.